1997
DOI: 10.1038/sj.bjp.0701036
|View full text |Cite
|
Sign up to set email alerts
|

Activation of endothelin ETA receptors masks the constrictor role of endothelin ETB receptors in rat isolated small mesenteric arteries

Abstract: 1 Endothelin-1 (ET-1) produces constriction of the rat mesenteric vascular bed in vivo via ET A and ET B receptor subtypes. The aim of this study was to investigate the relative roles of these receptor subtypes in rat isolated, endothelium-denuded, small mesenteric arteries, under pressure, by use of ET-1; the ET A receptor antagonist, BQ-123; the ET B receptor selective agonist, sarafotoxin S6c (SRTX S6c); the ET B receptor selective antagonist, BQ-788; and the ET A /ET B antagonist, TAK-044. 2 In 3rd generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 47 publications
3
69
1
Order By: Relevance
“…By blocking both receptor subtypes, bosentan may preserve the inter-play, while selective ET A receptor inhibition unbalances it. Previous investigators such as Mickley [29] and Adner [30] have previously reported the existence of an interaction between the two receptor subtypes in small mesenteric arteries. We have also recently demonstrated the existence of an interaction between the ET A and ET B receptor to induce the ET-1 vasoconstriction in pulmonary resistance arteries [17].…”
Section: Discussionmentioning
confidence: 94%
“…By blocking both receptor subtypes, bosentan may preserve the inter-play, while selective ET A receptor inhibition unbalances it. Previous investigators such as Mickley [29] and Adner [30] have previously reported the existence of an interaction between the two receptor subtypes in small mesenteric arteries. We have also recently demonstrated the existence of an interaction between the ET A and ET B receptor to induce the ET-1 vasoconstriction in pulmonary resistance arteries [17].…”
Section: Discussionmentioning
confidence: 94%
“…Another possibility is that cross talk exists between the 2 receptors, such that if only 1 receptor is blocked, the other receptor can compensate for the loss of activity. 23,24 Blockade of 1 of the receptors may attenuate an inhibitory action on the other receptor. 25 Such a mechanism may explain the potentiated effect of combined ET A and ET B receptor blockade in the atherosclerotic patients in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Venous ET A receptor blockade inhibited ET-1-induced contraction to a larger degree when ET B receptors were blocked, desensitized or non-functional (because of genetic disruption). Functional ET A and ET B receptor cross-talk occurs in other vessels including rat mesenteric veins (Claing et al 2002), rat isolated small mesenteric resistance arteries (Mickley et al 1997), mouse mesenteric veins (Perez-Rivera et al 2005), hamster saphenous and jugular veins (Lodge et al 1995), pulmonary arteries (Sauvageau et al 2006), and renal afferent arteries (Inscho et al 2006). All of these vessels, like the vena cava from wild-type rats, possess contractile ET A and ET B receptors, suggesting that pharmacological ET A and ET B receptor interaction may require the presence of contractile ET B receptors.…”
Section: Pharmacological Et a And Et B Receptor Interactionmentioning
confidence: 99%